PENINGKATAN DAYA SAING UMKM MELALUI PENERAPAN MANAJEMEN PEMASARAN DIGITAL BERBASIS MEDIA SOSIAL DI PAUH, KOTA PADANG - Malik, David; Wahyudi, Harry; Visza Adha, Howardi; Amrullah, Amrullah; Suandi, Edi; Suhanda, Mya Yuwanita (Komunitas Manajemen Kompetitif, 2024)
Micro, Small, and Medium Enterprises (MSMEs) play a crucial role in driving the local economy in Pauh District, Padang City. However, their development still faces marketing challenges, primarily because most businesses rely on conventional methods and have not yet fully utilized social media. Limited digital marketing knowledge, skills, and strategies result in low competitiveness in an increasingly competitive market. This Community Service Program aims to improve the competitiveness of MSMEs through the implementation of social media-based digital marketing management. Activities are implemented using a participatory approach through training, hands-on practice, and ongoing mentoring. The materials cover basic digital marketing concepts, engaging content creation, promotional and consumer interaction strategies, and simple marketing performance evaluations. The expected outcome is increased competency among MSMEs in managing social media accounts in a structured manner, expanding market reach, and increasing sales. Program outputs include training modules, activity reports, more effective social media account management, and scientific publications. On an ongoing basis, this program is expected to drive the digital transformation of MSMEs and strengthen local economic growth